“INCIDENCIA DEL TURISMO INTERNACIONAL EN EL CRECIMIENTO ECONÓMICO, PERÍODO 1995-2016: UN ENFOQUE DE DATOS DE PANEL APLICADO A 145 PAÍSES - Calva Castillo, Gina Viviana (2018)
International tourism is identified as one of the new and important sectors in economic growth, tourist arrivals and investment in this sector is translated into foreign exchange income, which at the same time represents great mobility and economic production in all the countries of the world, on the other hand the tourism industry appears as a positive alternative to mitigate and overcome economic adversities suffered by countries dependent on non-renewable natural resources and other sectors. This is why the research entitled "Impact of international tourism on economic growth, 1995-2016 period: a panel data approach applied to 145 countries" was carried out. Whose general objective was: to determine the incidence of international tourism on economic growth for 145 countries, period 1995-2016, through a descriptive and econometric study, with the purpose of establishing the effect on economic growth. The study had a global level approach, for 145 economies considering the productive structure of the countries, which was divided by High Income Countries (PIA), High Average Income Countries (PIMA), Low Average Income Countries (PIMB), and finally the Low Income Countries (PIB). It was done through the World Bank database (2017). It was found that international tourism has a stable short-term relationship in the economic growth of countries and in the long term it was only stable for 3 income groups, this balance ratio did not exist in the long term for low income countries (PIB). This last group means that a greater arrival of tourists, regardless of their level of income, is no longer a guarantee of prosperity if there is no security, infrastructure, social and economic stability for international tourism to generate great benefits in long-term economic growth.